Binomial Distribution As a Measurement of The Success and Failure FMIPA Untrib Students in The 2018-2023 Academic Year - Maktisen Ena; Jeni Marianti Loban; Narita Yuri Adrianingsih; Lois Letidena (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This research aims to determine the estimated probability of failure for the number of FMIPA Untrib Kalabahi student graduates from 2018 to 2023 for each study program. This research uses secondary data obtained directly from the Untrib Student Affairs Academic Administration Bureau for the last six years from 2018 to 2023. The Binomial Distribution is a distribution of discrete random variables with two possibilities, namely success and failure. This research shows that the three study programs at FMIPA Untrib Kalabahi have different opportunity or probability values. For the mathematics study program, it can be seen that the largest predicted failure will be in 2022, namely 0.225585937500 and the smallest predicted failure will be in 2019, namely 0.000000000015. For the chemistry study program, the biggest failure estimate is in 2023, namely 0.37500 and the largest failure estimate is in 2021, namely 0.00006. For the informatics engineering study program, the largest failure estimate is in 2018, namely 0.0000000298023223876953 and the smallest failure estimate is in 2023, namely 0.000000000000000087.